Spatial coverage of protection for terrestrial species under the Canadian Species at Risk Act. Issue 2 (2nd April 2020) - Bolliger, Clark S.; Raymond, Calla V.; Schuster, Richard; Bennett, Joseph R.
ABSTRACT: Canada's Species at Risk Act (SARA) has been critiqued for only protecting species on federal lands. However, this shortcoming has never been quantitatively assessed in terms of species' ranges. We assessed the proportion of ranges of federally-listed terrestrial species at risk (SAR) receiving protection via SARA, excluding birds protected by the Migratory Birds Convention Act. Additionally, we assessed species protection provided by provincial and territorial protected areas within the ranges of SARA-listed species. We show that federal land provides protection within only 8.1% of species' Canadian ranges on average, and 63.1% of 252 terrestrial SAR are protected within less than 5% of their range. The addition of provincial and territorial protected areas increases this average to 14.6% and reduces the percent with less than 5% protection to 34.9% of species. Eighteen species receive 0% protection within their Canadian ranges. We found no significant difference in average protection among taxonomic groups. Canada's capacity to protect SAR via SARA could be improved by greater coordination among national, provincial and Indigenous governments, the creation of a more effective protected area network, exercising SARA's provision for emergency protection orders where applicable, and facilitating greater SAR protection on public and private lands.